Peningkatan Literasi Masyarakat melalui Pojok Baca di Balai Desa Umbulrejo - Ernanda Cindy Wahyuningrum; Syamsul Anam; Abdul Jalil; Silvi Izzun Nisa; Arinta Trulyana; Alifia Oktahariana; Nur Laila; Ervina Ismiatul Hasanah; Nila Himah Muddah; Anik Nuzulur Rohmah; Aulia Maidatur Rohmah; Ela Nur Afifah; Alfiatul Laily; Rofiq Hidayat (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2022)
Abstract: The activity of placing the Reading Corner as an effort to support the increase in people's reading interest in the Umbulrejo village hall is a community service activity that is motivated by a joint effort to increase literacy and interest in reading among the village community because the Umbulrejo village hall does not provide a reading corner. This program aims to improve people's literacy skills with the support of a reading corner as well as being able to bring reading materials closer to the community while at the Umbulrejo village hall. The implementation method used in community service includes the method of discussion, promotion and placement of a reading corner at the village hall. This activity involved village officials in the discussion and promotion process as well as the community so that on the first day after the initial laying of the reading corner the number of visitors was quite large, namely 16 people and the visitor's response was very positive and felt lucky because at the village hall there was already a reading corner which not only benefits the village but also the Umbulrejo community in improving reading literacy in Umbulrejo village. Keywords: literacy, Reading Corner, Village Hall